Radial variation of wood functional traits reflect size‐related adaptations of tree mechanics and hydraulics. (11th September 2017) - Rungwattana, Kanin; Hietz, Peter
Abstract: Wood serves for mechanical support, water transport and storage. These functions are provided for by different cells with a large variation in wood anatomy among species but also within individual trees. The latter often reflects ontogenetic adjustments, related to tree size or age, which can be studied by looking at patterns of radial variation in wood. We quantified radial variation in wood density (WD) and wood anatomy and ask how ontogenetic changes of wood functions are controlled in five canopy tree species in western Thailand. We ask if there are trade‐offs between these main functions of wood, how ontogenetic trends are linked to differences in growth trajectories and shade tolerance among tree species and if wood properties are mainly controlled by tree age or by size. In all species studied, vessel fraction, vessel size, theoretical hydraulic conductivity ( K h ) and fibre wall thickness significantly increased with tree diameter. While the ray fraction also increased in all species except Neolitsea, axial parenchyma changed significantly only in Afzelia, the species with by far the largest axial parenchyma fraction. The average WD and K h reflect the phenology, with deciduous and shade‐intolerant Toona and Melia having low WD and high K h, and shade‐tolerant brevi‐deciduous Chukrasia and evergreen Neolitsea having higher WD and low K h . Deciduous Afzelia, however, had the lowest K h and second‐highest WD. The radial gradients in WD and K h also reflect within‐species differences in growth rates during ontogeny. The relationship between WD and its underlying anatomical components varied substantially among species. Modulating fibre wall thickness and vessel size enables growing trees to increase water transport capacity and mechanical strength at the same time. Across species, tree diameter had a stronger effect than age on all parameters except for fibres. Given the very substantial within‐tree size‐related variation in wood traits, tree size is an essential parameter to include in comparative studies on the functional ecology of wood. Analysing ontogenetic changes in wood can advance our understanding of the different ecological strategies of trees. A plain language summary is available for this article. Abstract : Plain Language Summary